Dampak Pertumbuhan Laba, Struktur Modal dan Likuiditas terhadap Kualitas Laba - Tiara Tri Amanda; Erinos NR (Universitas Negeri Padang, 2023)
This study aims to examine the effect of profit growth, capital structure, and liquidity on earnings quality. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sample was determined based on the purposive sampling method, in order to obtain 65 companies. The source of data in this study is secondary data, that obtained using the documentation observation method at www.idx.co.id. The data analysis technique used is multiple linear regression. The results of this study indicate that profit growth has no effect on earnings quality, while capital structure has a significant negative effect on earnings quality and liquidity has a significant positive effect on earnings quality.